2001
DOI: 10.1007/s100480100113
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to MS: a second stage analysis in Canadian MS families

Abstract: Four published genome screens have identified a number of markers with increased sharing in multiple sclerosis (MS) families, although none has reached statistical significance. One hundred and five markers previously identified as showing increased sharing in Canadian, British, Finnish, and American genome screens were genotyped in 219 sibling pairs ascertained from the database of the Canadian Collaborative Project on Genetic Susceptibility to MS (CCPGSMS). No markers examined met criteria for significant li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…Adding more microsatellite markers to the initial genome screens also failed to produce new MS-associated genes Dyment et al, 2004b;Kenealy et al, 2004). Pooling data for meta-analysis was similarly of no help in identifying loci other than the MHC (Dyment et al, 2001;GAMES, Transatlantic Multiple Sclerosis Genetics Cooperative, 2003). Consequently, it became clear that the identification of the other effects of genetic variations impacting MS susceptibility would require not only better markers but also a substantially increased number of families to reach necessary statistical power.…”
Section: Genomic Linkage Screensmentioning
confidence: 99%
“…Adding more microsatellite markers to the initial genome screens also failed to produce new MS-associated genes Dyment et al, 2004b;Kenealy et al, 2004). Pooling data for meta-analysis was similarly of no help in identifying loci other than the MHC (Dyment et al, 2001;GAMES, Transatlantic Multiple Sclerosis Genetics Cooperative, 2003). Consequently, it became clear that the identification of the other effects of genetic variations impacting MS susceptibility would require not only better markers but also a substantially increased number of families to reach necessary statistical power.…”
Section: Genomic Linkage Screensmentioning
confidence: 99%
“…1 The prevalence pattern may be explained, at least in part, by migrations of northern European groups and their descendants which strengthens the hypothesis of genetic factors contributing to MS. 2 Epidemiological studies performed in twins and siblings clearly indicate the impact of genetic factors. 3,4 In addition, the geographical distribution of MS and studies of migrants also suggest a considerable contribution of environmental factors that may not be evenly distributed over the world.…”
Section: Introductionmentioning
confidence: 99%
“…A combined genomic map of MS was constructed using 170 microsatellite markers or regions previously reported in whole genome linkage screens 2-14 and their follow-up studies, [20][21][22][23][24][25] and 263 'top-ranked' markers reported in the case-control association studies of the GAMES project. 15 These markers or regions were selected based on the statistics reported in the original studies, including both significant and suggested occurrences.…”
Section: Resultsmentioning
confidence: 99%